New steering concepts in public management - Groeneveld, Sandra, 1972-; Van de Walle, Steven (Bingley, U.K. : Emerald, 2011)
Multifaceted social problems such as safety, social inclusion, poverty, mobility, rural development, city regeneration, or labour market integration require integrated approaches to steering. NPM-related fragmentation of policy and fragmentation of implementation lead to unsatisfactory public outcomes and a heightened experienced loss of control on the part of policy makers. Governments are therefore looking for new instruments to address the boundary-spanning nature of many social problems. In their quest for achieving valued social outcomes, they struggle with their new role, and the insufficiency of both markets and hierarchies. In this book, authors explore new organisational mechanisms, arrangements and ideas to deal with this fragmentation. New post-NPM steering and coordination practices come in various shapes and names, and current research suffers from considerable terminological confusion. The book first looks at various new organisational arrangements and mechanisms, including whole-of-government, collaborative governance, network governance, and outcome steering. It then goes on to unpack the outcomes these new steering instruments are supposed to achieve, and explores their effect on democracy, power, and the role of government.
ch. 1. Introduction / Sandra Groeneveld, Steven Van de Walle -- ch. 2. Post-NPM reforms : whole of government approaches as a new trend / Tom Christensen, Per L$1!P[(Bid -- ch. 3. The empty nest syndrome : Dutch ministries after the separation of policy and administration / Sandra van Thiel -- ch. 4. Assessing public networks : proposal for a new unit of analysis / Tamyko Ysa, Marc Esteve -- ch. 5. Steering societal resilience : an empirical exploration of trends and challenges in government-citizen collaboration / Philip Marcel Karr Martijn van der Steen, Mark van Twist -- ch. 6. Steering emergent and complex change processes / Walter Kickert -- ch. 7. Outcome-based service commissioning and delivery : does it make a difference? / Tony Bovaird, Rhodri Davies -- ch. 8. The direct engagement of citizen users through assessment, choice and evaluation of welfare services : the implications of the personalisation agenda / Alex Murdock -- ch. 9. The UK obesity epidemic : new steering instruments for a new public policy problematic? / Josie Kelly -- ch. 10. Steering outcomes in urban regeneration projects : an empirical study of a Hui community in China / Jiannan Wu, Yuqian Yang, Liang Ma -- ch. 11. Steering for social outcomes in governance networks : the effects of participation and network management / Erik-Hans Klijn, Bram Steijn, Jurian Edelenbos, Brenda Vermeeren -- ch. 12. In search of network performance / Joris Voets, Wouter Van Dooren -- ch. 13. New steering instruments : trends in public sector practice and scholarship / Steven Van de Walle, Sandra Groeneveld.s
Includes bibliographical references.
Keywords: Public administration